Prehistoric Rain Cookies: Geological-Inspired Culinary Creation Promoting Local Socio-Cultural and Economic Empowerment - Dina Tania; Herry Riswandi (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents the development and implementation of a community engagement project centered around the creation of "Prehistoric Rain Cookies." The project was undertaken in Desa Lempong, Kecamatan Jenawi, Kabupaten Karanganyar, Provinsi Jawa Tengah, situated in the vicinity of Mount Lawu, Indonesia. The primary goals of the project were twofold: first, to incorporate geological inspiration from ancient volcanic rock formations into culinary art, specifically in the form of unique cookies; and second, to foster geotourism combined with ecotourism as a means of empowering the local community socially, culturally, and economically. Through a series of direct interviews with the Lempong community, the most sought-after products by tourists visiting Mount Lawu were identified. Subsequently, the selected product, "Prehistoric Rain Cookies," was developed to resemble the accretionary lapilli rock formations found in the area. The cookies were packaged in two distinct shapes to resemble the original rock formations further. Legal procedures were followed, including copyright registration, to ensure the protection of the cookie creation. The project concluded with the handover of the cookies to the Lempong Village authorities, aiming to inspire local innovation, enhance cultural and economic growth through ecotourism, and serve as a geological educational tool for visitors to Mount Lawu. The implications of this project highlight the potential for incorporating scientific research findings into culinary creations to promote local empowerment and stimulate geotourism initiatives. Highlight: Geological-inspired culinary art: The creation of "Cookies Hujan Purba" embodies the desire to incorporate inspiration from natural rock formations into culinary creations, showcasing the fusion of geology and gastronomy. Geotourism and ecotourism synergy: The project aims to promote geotourism and ecotourism in the Lempong Village, offering educational experiences to visitors while supporting socio-cultural and economic empowerment within the local community. Socio-cultural and economic empowerment: By developing and marketing the Prehistoric Rain Cookies, the project seeks to empower the local community socially and economically, fostering pride in their cultural heritage and creating opportunities for sustainable growth. Keyword: Lawu Ancient Rain Cookies, Geological-Inspired Culinary Creation, Geotourism, Socio-Cultural Empowerment, Local Economic Development